2018
DOI: 10.14744/anatoljcardiol.2018.90001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of stand-alone transthoracic echocardiography-guided percutaneous occlusion of patent ductus arteriosus

Abstract: Objective:We aimed to investigate the feasibility and safety of stand-alone transthoracic echocardiography-guided percutaneous occlusion of patent ductus arteriosus (PDA) without the use of X-ray equipment.Methods:From January to December 2015, we performed stand-alone transthoracic echocardiography-guided percutaneous PDA occlusion using an occluder delivered via a delivery sheath introduced via femoral vein access without the use of X-ray equipment in 12 PDA patients.Results:PDA occlusion was successfully pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Binobaidan et al ( 12 ), Cao et al ( 20 ), and Ye et al ( 21 ) showed success rates of 100% in PDA closure, while only Zhang et al ( 22 ) showed a success rate of 97.1%. These results were similar to our study in which all the procedures were successful in both echocardiography and fluoroscopy groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Binobaidan et al ( 12 ), Cao et al ( 20 ), and Ye et al ( 21 ) showed success rates of 100% in PDA closure, while only Zhang et al ( 22 ) showed a success rate of 97.1%. These results were similar to our study in which all the procedures were successful in both echocardiography and fluoroscopy groups.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to our study in which all the procedures were successful in both echocardiography and fluoroscopy groups. Most studies showed no residual shunt and severe complications after 1 month to 2 years of follow-up ( 12 , 20 – 22 ). Pan et al had 8 cases of small residual shunts in 24 h but resolved afterward ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study demonstrated successful transcatheter ductal closure guided only by TTE. Previously published studies have demonstated acceptable reliability of this procedure [9,10]. Our research focused on PDA closure for pediatric patients under the guidance of TTE alone.…”
Section: Discussionmentioning
confidence: 99%
“…Oto et al ( 15 ) demonstrated the efficacy and safety of TTE guidance during percutaneous device closure of patent foramen ovale, demonstrating a shortened procedural time without the need for general anesthesia or endotracheal intubation. We also used TTE to guide transthoracic device closure of ASDs and transcatheter device closure of patent ductus arteriosus with satisfactory results ( 16 , 17 ). Increasing the number of investigators confirmed that TTE can be used as a reliable tool for guidance during device closure by skilled hands.…”
Section: Discussionmentioning
confidence: 99%